Desenvolvimento de sistemas à base de mesocarpo de babaçu e alginato de sódio como matriz carregadora do fármaco metronidazol - OLIVEIRA, Letícia Nascimento de (2021)
This work aimed to evaluate spheres based on sodium alginate and starch extracted from babassu mesocarp as a matrix for the controlled release of the drug metronidazole. The starch was obtained by water extraction method and the same was synthesized using chloroacetic acid as etherifying agent, resulting in carboxymethylamides with degrees of substitution (GS) of 0.15 ± 0.01 and 0.3 ± 0.01. The solubility and intumescence study of the starch and carboxymethylamide samples showed changes in the properties after modification. The study of amylose content of native and modified starch using colorimetric method showed a large variation in amylose content, from 28.0 ± 0.89, 4.70 ± 0.21 and 3.32 ± 0.04, proving the reduction of the macromolecule after modification. The starch and carboxymethyl starch samples were characterized by FTIR, SEM and DSC. The drug metronidazole was incorporated into sodium alginate/ babassu mesocarp starch and sodium alginate/carboxymethyl starch polymeric matrices, obtaining spheres through ionotropic gelation in a CaCl2 solution. The interaction between the polysaccharides and the incorporation of the drug were proven by FTIR and SEM results. Energy Dispersive Spectroscopy (EDS) analysis enabled the detection of elements such as Ca, Na, Cl and O, as well as the percentage changes that occurred after polymer mixing. A molecular absorption study in the ultraviolet region proved the presence of the drug metronidazole incorporated in the spheres. The study of intumescence and erosion of the spheres showed that the absorption capacity of the spheres was improved in the spheres containing the CMA, which also influenced the erosion that was decreased with the increase in the degree of substitution of the anionic starch. The encapsulation efficiency (EE) varied according to the composition of the spheres. For the alginate and alginate/raw starch spheres the EE was 36.0% ± 5.40 and 53% ± 4.23 and for the alginate/carboxymethyl starch spheres, the EE obtained was 69.57% ± 3.94 and 73.89% ± 5.22. The release assays demonstrated that in gastric medium, the spheres showed a low dissolution rate, suggesting gastroresistance at low pH. In simulated enteric medium, the ALG.CMA2 samples (GS = 0.3) maintained the same dissolution rate until the end of the experiment, suggesting a control in the release of metronidazole. Thus, it was possible to prove that the samples containing carboxymethyl starch are promising delivery systems for the sustained release of the drug under gastrointestinal conditions.